RESEARCH ON THE PROCESS OF EXTRACTING PECTIN FROM DOLANA FRUITS - Gulamkhodzaeva N. Kh. (Web of Journals Publishing, 2025)
Proper nutrition based on a consistent diet alleviates many digestive diseases and helps prevent serious conditions such as gastritis and stomach ulcers. Proper nutrition also positively affects hormone synthesis, normalizing their balance. As a result, the human body begins to sleep better and can function much better throughout the day. [1]. Nutritional fibers such as pectins, cellulose, hemicellulose, tooth meat, mucilage, and non-carbohydrate compounds like lignin are non-digestible polysaccharides that cannot be digested in the small intestine. Additionally, they include pentosans, chitin, chitosan, and some amino sugars from fungi and crustaceans that are indigestible proteins. [2]. Malnutrition is a risk factor for diseases such as colon cancer, irritable bowel syndrome, constipation syndrome, hypomotor dyskinesia of the large intestine, diverticulosis, appendicitis, diaphragmatic hernia, cholelithiasis, diabetes mellitus, obesity, atherosclerosis, cardiovascular diseases, hyperlipoproteinemia, varicose veins, and thrombosis of the lower limbs. [3]. The purpose of the research: To investigate the processes of obtaining pectin substances from the fruits of the C. songarica and C. turkestanica groups that grow in Uzbekistan.
Keywords: Pectin, oxalic acid, ammonium oxalate, capron membranes, ions, chromatography, aniline-phthalate, pentoses, uronic acids, hexoses.